2015
DOI: 10.1186/s12889-015-2410-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of China’s new rural cooperative medical system: achievements and inadequacies from policy goals

Abstract: BackgroundAlthough much public scrutiny and academic attention has focused on the evaluations of system implementation since the beginning of New Rural Cooperative Medical System (NRCMS) in China, few studies have systematically evaluated the achievements of the stated policy goals. The purpose of this study is to examine to what extent the policy goals of NRCMS have been achieved.MethodsUsing multistage sampling processes, two rounds of cross-sectional household surveys including 9787 and 7921 rural household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Focusing on the new rural co‐operative medical system for farmers, Li et al . () found that this programme has only achieved limited positive effects in regards to household financial risk from medical expenses and rural‐urban income inequity. In 2007, 4.9 hospital beds were available for every 1,000 urban residents, but only two hospital beds were available for every 1,000 rural residents.…”
Section: Regional Fragmentation Of the Chinese Social Modelmentioning
confidence: 99%
“…Focusing on the new rural co‐operative medical system for farmers, Li et al . () found that this programme has only achieved limited positive effects in regards to household financial risk from medical expenses and rural‐urban income inequity. In 2007, 4.9 hospital beds were available for every 1,000 urban residents, but only two hospital beds were available for every 1,000 rural residents.…”
Section: Regional Fragmentation Of the Chinese Social Modelmentioning
confidence: 99%
“…In this study, all children came from low-income rural families in the province of Anhui, China, and were supported by the NRCMS, one of the world's largest basic medical insurance schemes, mandated by China's Ministry of Health, and implemented by local and provincial governments (15). All families participating in our cost-utility substudy were reimbursed 70% of the CI system costs (CNY 119,000, USD 17,850), through the NRCMS.…”
Section: Discussionmentioning
confidence: 99%
“…For rural residents of Anhui Province, China, 70% of the combined costs of CI system and hospital episode were reimbursed through the New Rural Cooperative Medical System (NRCMS) of China (15). Initial costs considered in the economic model included direct medical costs related to hospital stay, salaries of ward medical and ward nursing staff, allied health, imaging, pathology, pharmacy, critical care, operating theatre, anaesthesia and consumables, nursing and ward supplies, and other minor bed costs.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically speaking, the loan ratio for China's commercial banks for farmers and agricultural organizations and business is very low. It is reported that the loan that the Agricultural Bank invested in rural areas accounted for only 10% of the amount of total loans [5]. Although over the past 50 years, the rural credit cooperatives have become a part of the financial system of our country, and it plays an important role in meeting the needs of the farmers.…”
Section: Lack Of Financing Channelsmentioning
confidence: 99%